Towards a Data on the Web Lifecycle Model - Silva, Karina Moura; Oliveira, Marcelo Souza; Lóscio, Bernadette Farias (Anais do Simpósio Brasileiro de Sistemas de Informação (SBSI); 2020: Anais do XVI Simpósio Brasileiro de Sistemas de InformaçãoDO - 10.5753/sbsi.2020.13787, 2020)
Due to its exponential growth, the Web has become an important platform for sharing and exchanging data. Several methodologies, guidelines and good practices have been proposed to ease and guide users to consume and publish data on the Web. However, there is still a shortage of initiatives to clearly define the phases the data travels through the Web. Lifecycle models could be proposed to fill this gap. In this context, this paper proposes a Data on the Web Lifecycle Model, which aims to clearly specify the roles, phases and activities regarding Data on the Web publishing and consuming.